The Search for Truth: A Psychological Analysis of Bulgarian Children’s Adaptation to the Portuguese Language Environment with a Special Focus on Translanguaging - Matelova, Bojana (Innovare Journal of Education, 2023)
There is an increasing migration from Bulgaria to Brazil. The group of migrants is very homogenous since they arrive with the same aim of working and saving money for a better future at home in Bulgaria. The statistics reveal that the migrants often arrive with families, including children, who must attend compulsory schools in Brazil. According to Brazilian law, all children are entitled to education in the Portuguese language. This creates many problems for newly arrived families who have limited knowledge of Portuguese. This paper investigates Bulgarian children’s meta-language and translanguaging approaches during official schooling and extracurricular activities. The theoretical framework is grounded in the theories about translanguaging and second language development of newly arrived children. The participants of the study are 55 Bulgarian children who were observed in various environments: at schools, at home and during extracurricular activities with peers. The main findings paint an interesting pattern of the various ways to convey the meaning through translanguaging depending on the contextual situation.